Effects of typical flotation reagent on microbial toxicity and nickel bioavailability in soil. (February 2020) - Li, Hao; Yao, Jun; Duran, Robert; Roha, Beenish; Karapınar, Nuray; Jordan, Gyozo; Minkina, Tatiana; Gu, Jihai; Lu, Chao; Min, Ning; Fan, Zixia
Abstract: The combined toxicological effects of nickel (Ni) and butyl xanthate (BX), that is commonly used in flotation reagents for non-ferrous metals ore processing such as Ni, copper and lead ores, on soil microbial communities were studied by determining soil microbial activity, soil enzyme activities and Ni bioavailability. The results revealed that the exchangeable (EXC) and reducible (RED) fractions of Ni were higher in Ni/BX mixture than Ni alone, probably because BX reacts with Ni to form complexes that lead an increase in bioavailability of Ni. The presence of BX and Ni inhibited microbial activity and enzyme activities during the first 30-days. Then, from 30 days to 180 days, different trends were observed according to the condition: microbial activity was stimulated with BX alone while it was inhibited with Ni/BX mixture. This observation was supported by the fact that the inhibitory ratio ( I ) was higher for Ni/BX mixture than BX alone. Results showed that the sensitivity to one or both contaminants followed the order: urease (UA) > invertase (INV). EXC fraction of Ni/BX mixture were significantly correlated with UA, INV, I, peak power ( P peak ) and peak time ( T peak ), respectively ( p  < 0.01), suggesting that Ni bioavailability might explain the Ni toxicity against microbial communities under combined pollution conditions. Such observations allow us to better understand toxic effects of Ni pollution when accompanied with BX, facilitating precisely evaluation of potential risks in mining areas. Highlights: Ni was transferred to stable fractions in absence of flotation reagent BX. BX facilitates the Ni transfer to bio-available fractions increasing its toxicity. Ni and BX showed long-term toxic effects on soil microbial activity. Biological activities correlated significantly with bioavailable Ni-EXC fraction.